Indoor green wall affects health-associated commensal skin microbiota and enhances immune regulation: a randomized trial among urban office workers - Soininen, L.; Roslund, M. I.; Nurminen, N.; Puhakka, R.; Laitinen, O. H.; Hyöty, H.; Sinkkonen, A. (Scientific reports, 2022)
Urbanization reduces microbiological abundance and diversity, which has been associated with immune mediated diseases. Urban greening may be used as a prophylactic method to restore microbiological diversity in cities and among urbanites. This study evaluated the impact of air-circulating green walls on bacterial abundance and diversity on human skin, and on immune responses determined by blood cytokine measurements. Human subjects working in offices in two Finnish cities (Lahti and Tampere) participated in a two-week intervention, where green walls were installed in the rooms of the experimental group. Control group worked without green walls. Skin and blood samples were collected before (Day0), during (Day14) and two weeks after (Day28) the intervention. The relative abundance of genus Lactobacillus and the Shannon diversity of phylum Proteobacteria and class Gammaproteobacteria increased in the experimental group. Proteobacterial diversity was connected to the lower proinflammatory cytokine IL-17A level among participants in Lahti. In addition, the change in TGF-β1 levels was opposite between the experimental and control group. As skin Lactobacillus and the diversity of Proteobacteria and Gammaproteobacteria are considered advantageous for skin health, air-circulating green walls may induce beneficial changes in a human microbiome. The immunomodulatory potential of air-circulating green walls deserves further research attention.